Alternative sigma factor RpoN and its modulation protein YhbH are indispensable for Erwinia amylovora virulence - Ancona, Veronica (Mol Plant Pathol, 2013)
In Erwinia amylovora, ECF (extracytoplasmic functions) alternative sigma factor HrpL regulates the transcription of hrp (hypersensitive response and pathogenicity)‐type III secretion system (T3SS) genes by binding to a consensus sequence known as the hrp box in hrp gene promoters. In turn, the expression of hrpL has been proposed to be positively controlled by alternative sigma factor 54 (σ(54)) (RpoN) and HrpS, a member of the σ(54) enhancer‐binding proteins (EBPs). However, the function of RpoN has not been characterized genetically in E. amylovora. In this study, we investigated the role of RpoN, a nitrogen limitation sigma factor, and its modulation protein YhbH, a novel ribosome‐associated protein, in E. amylovora virulence. Our results showed that mutations in hrpS, hrpL, rpoN and yhbH, but not yfiA and rmf3, resulted in a nonpathogenic phenotype on immature pear fruits and apple shoots. Consistently, the expression of T3SS genes, including hrpL, dspE, hrpN and hrpA, was barely detected in hrpS, hrpL, rpoN and yhbH mutants. These mutants were also not capable of eliciting a hypersensitive response (HR) on tobacco; however, the overexpression of hrpL using an inducible promoter rescued the HR‐eliciting abilities of these mutants. These results suggest that a sigma factor cascade exists in the regulatory networks of E. amylovora and regulates important virulence factors. On the basis of this study and previously reported data, a model is proposed for the regulation of T3SS in E. amylovora.